Penerapan Permainan Monosean Go untuk Meningkatkan Motivasi Belajar IPS Siswa Kelas VI SD Negeri 060913 Medan - Rahmi, Siti Syafrida; Mushlihuddin, Rahmad; Maronipta, Zulia (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on game-based learning media, despite its significant impact on student engagement and motivation, particularly in social studies (IPS) education. The study aims to assess the effectiveness of the educational game Monosean Go in enhancing the learning motivation of sixth-grade students in IPS. The method used is Classroom Action Research (CAR), conducted over two cycles with a sample of 20 students selected through purposive sampling. Data were collected through observation sheets, motivation questionnaires, and documentation, and analyzed descriptively using percentage techniques. The results show an increase in student learning motivation from 59% (low category) in the initial condition to 67% (moderate category) in Cycle I, and reaching 86% (very high category) in Cycle II. These findings support learning motivation theories that emphasize the importance of interactive, student-centered learning. The study concludes that the Monosean Go game is effective in enhancing student learning motivation. Its implications include contributing to the literature on game-based learning and offering practical recommendations for teachers to integrate contextual learning media to create more engaging and meaningful learning experiences. The study also opens opportunities for further research on the long-term impact and adaptation of similar games in different subjects and educational levels.